Comparing attitudes of younger and older patients towards cancer clinical trials. Issue 3 (May 2016) - Ayodele, Olubukola; Akhtar, Mateen; Konenko, Aiste; Keegan, Niamh; Calacsan, Flordeliza; Duggan, Lesley; O'Connor, Miriam; Calvert, Paula; Townsley, Carol A.; Horgan, Anne M.
Abstract: Objectives: To determine the attitudes of patients towards cancer clinical trials (CCTs) and assess the differences between older and younger patients. Materials and Methods: Patients with cancer, receiving treatment or in follow-up in University Hospital Waterford, Ireland were eligible. Patients completed a self-administered questionnaire. To determine attitudes towards CCTs, patients indicated their preference if offered participation in three hypothetical studies (cancer prevention/screening trial; CCT comparing standard to new treatment; a trial of new drug where no standard exists). Patients' reasons to or not to participate in CCTs were explored. Results: From May 2014 to March 2015, 219 patients were accrued, 119 < 65 years and 100 ≥ 65 years. Twenty-two (18%) younger and 4 (4%) older patients had been/were actively enrolled on a CCT ( p = 0.0012). No older patient and 5 (4%) of younger patients had enquired about CCT availability. For the CCT questions, 85 (71%) younger vs 57 (57%) older patients would participate in a prevention/screening CCT ( p = 0.033); 60 (50%) vs 44 (44%) for standard vs new drug ( p = 0.415), and 83 (69%) vs 78 (78%) for a CCT where no standard exists ( p = 0.218). The most common reason to participate in a CCT was a recommendation from the oncologist − 98% < 65 years vs 87% ≥ 65 years ( p = 0.001), with health problems being the leading reason not to participate, 86% vs 72% ( p = 0.01), respectively. Conclusions: Older and younger patients in this study gave similar importance to reasons for and against participation in CCTs. Most patients did not actively seek out a CCT, which may reflect a lack of awareness and a need for better education.